Antioxidant characteristics of tea-herbal compositions - Kuzmin, Oleg; Stukalska (Ivanova), Nataliia; Mykhonik, Larysa; Koval, Olga; Polovyk, Volodymyr; Berezova, Ganna (My University, 2021)
The aim of the study was to determine the antioxidant capacity of herbal infusions and evaluate the possibility of using them to create herbal tea compositions. Antioxidant capacity of tea-herbal compositions was determined by redoxmetry and pH-metry; sensory indicators were evaluated by expert method; results of mathematical and statistical processing were assessed by the method of linear Pearson correlation. The рН for water infusions from raw materials has a value of 2.35 for Hibiscus sabdariffa and 6.55 for Calamintha nepeta. The minimum theoretical value of RP (Ehmin) for plant water infusions was obtained, which has a value from 267.0 mV for Calamintha nepeta to 519.0 mV for Hibiscus sabdariffa. The actual measured RP of infusions (Ehact) was established as 37.0 mV for Daucus carota and 203.0 mV for Hibiscus sabdariffa. Water infusions from vegetable raw materials have the value of regenerative capacity (recovery energy, REinf) in the range from REinf 150.8 mV for Vitis vinifera) to REinf 316.0 mV for Hibiscus sabdariffa. For the restaurant business in the manufacture of beverages are promising water infusions of Hibiscus sabdariffa and Citrus limonum, which received increased antioxidant characteristics REinf 316.0 mV and 298.0 mV, respectively, and positive sensory evaluation. It is proved that the energy of reduction/oxidation of vegetable raw materials (REplant) relative to the solvent – prepared water is in the range of values from 45.8 mV for Vitis vinifera to 211.0 mV for Hibiscus sabdariffa. Based on mathematical and statistical analysis, it was found that physicochemical parameters in the range of values with very high correlation (r 0.9–1.0) includes the following indicators: pH, Ehmin, REinf, REplant. Rational composition of tea-herbal composition was found: Hibiscus sabdariffa, 30 %; Matricaria chamomilla, 20 %; Ilex paraguariensis, 10 %; Rosae fructus, 10 %; Mentha piperita, 10 %; Citrus sinensis, 8 %; Citrus limonum, 7 %; Calendulae flores, 5 %. For the technology of the restaurant industry, the use of tea-herbal compositions from plant materials Hibiscus sabdariffa, Matricaria chamomilla, Ilex paraguariensis, Rosae fructus, Mentha piperita, Citrus sinensis, Citrus limonum, Calendulae flores, which have increased antioxidant characteristics, is proposed.
Keywords: herbal tea; трав'яний настій; antioxidants; redox potential; кафедра технології ресторанної і аюрведичної продукції; кафедра технології хлібопекарських і кондитерських виробів; трав'яний чай; herbal infusion; антиоксиданти; окисно-відновний потенціал